Official visit of Prime Minister Atal Bihari Vajpayee to the United States September 13-17, 2000 - United States (New Delhi, 2000)
This book cover following topics Speeches & Statements, Agreements and Foreign relations India-United States.
Keywords: "Vajpayee, Atal Bihari"